PENYULUHAN DAN PELATIHAN PEMASANGAN INSTALASI LISTRIK RUMAH TANGGA DI PONDOK PESANTREN MAMBAUL HIKMAH DUSUN SUMBERSARI DESA SUMBERKARANG KECAMATAN DLANGGU MOJOKERTO - Sutikno, Sutikno (Universitas Respati Yogyakarta, 2021)
Lack of public knowledge about electricity, many people repair electrical installations that are not in accordance with the existing provisions of the government. So that it can be the safety of humans and the environment. The majority of the residents of Sumberkarang and main Pondok Pesantren Mambaul Hikmah consist of various occupations ranging from lecturers, teachers, entrepreneurs, traders, factory employees, and farmers. Nowadays electricity is one of the basic necessities that cannot be separated. Electricity can be used for daily needs or for business. But if you can't go up and take care of it, electricity can endanger lives and even life and property. Many fires occur because of this short circuit, the ground wire is not installed or installed, but the resistance is too large. Based on a field survey, the villagers around the cottage still do not really understand the electricity installation. They do not understand the dangers and disturbances of electricity. People only know about this method, lights, turn on pumps, television and so on. With a brief analysis, I hereby as a teacher provide, convey knowledge both in theory and practice so that people have knowledge about electricity, which can provide electricity for the benefit of stairs. or efforts can prevent harm preventionKeywords : Electric danger, hydrogen